Muslims In Australia. - Kabir, Nahid (Taylor and Francis, 2013)
Muslims in Australia investigates the basis of Australian society's fear of Muslims by tracing their history since the Afghan settlement in 1860. The author investigates how events such as September 11 and Bali terrorist attacks reinforce suspicion and fear, giving an insight into what it means to be a Muslim in contemporary Australia, and how the actions of militant Islamic groups have impacted upon Muslims in general in Western society.